2001
DOI: 10.1056/nejm200103293441304
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Recurrent Upper Gastrointestinal Bleeding in Patients withHelicobacter pyloriInfection Who Are Taking Low-Dose Aspirin or Naproxen

Abstract: Among patients with H. pylori infection and a history of upper gastrointestinal bleeding who are taking low-dose aspirin, the eradication of H. pylori is equivalent to treatment with omeprazole in preventing recurrent bleeding. Omeprazole is superior to the eradication of H. pylori in preventing recurrent bleeding in patients who are taking other NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
305
3
26

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(340 citation statements)
references
References 19 publications
6
305
3
26
Order By: Relevance
“…Among those taking LDA, especially references with respect to the probability of recurrent bleeding, the eradication of H. pylori is equivalent to treatment with omeprazole [131].…”
Section: Commentmentioning
confidence: 99%
“…Among those taking LDA, especially references with respect to the probability of recurrent bleeding, the eradication of H. pylori is equivalent to treatment with omeprazole [131].…”
Section: Commentmentioning
confidence: 99%
“…In this scenario, using a proton pump inhibitor is better than simply eradicating the bacteria (19) . The best protection for the patient in these cases is to apply both, namely, the proton pump inhibitor and eradicating H pylori (20) .…”
Section: Statement 24mentioning
confidence: 99%
“…The best approach in these cases, besides eradicating H pylori, is to indicate the maintenance use of proton pump inhibitors (19,114) .…”
Section: Statement 24mentioning
confidence: 99%
“…In addition, studies conducted in Hong Kong and the US have revealed that both H pylori eradication [3] and PPI treatment [4] are useful in preventing the recurrence of hemorrhagic peptic ulcers induced by low-dose aspirin. In Japan, however, the administration of PPIs, H2RAs and prostaglandins for the prevention of peptic ulcers induced by NSAIDs and low-dose aspirin is not covered by medical insurance, although the use of these drugs for the treatment of peptic ulcers is covered.…”
Section: Discussionmentioning
confidence: 99%